Nonlinear dynamics of speculative attacks on the Finnish markka, 1987-1992 - Risto Murto (Bank of Finland, 1994)
In this paper, I estimate nonlinear autoregressive models for Finnish short-term interest rates using daily data.The nonlinear models considered in the paper are the logistic (LSTAR) and exponential (ESTAR) autoregressive models.The estimated LSTAR model appears to capture some of the interest rate dynamics associated with the speculative attacks against the Finnish markka.The combined LSTAR-GARCH models are also estimated.
URN:NBN:fi:bof-20140807495
Keywords: 330